Perancangan Website Sebagai Media Promosi Digital Pada UMKM Ladu Arai Pinang One - Ulfa Ramadhani; Rizka Apriani Putri; Nacwa Tipani HN; Sularno .; Novadilastri . (CV. ITTC INDONESIA, 2026)
Advancements in information technology have significantly impacted various business sectors, including Micro, Small, and Medium Enterprises (MSMEs). One way technology can support MSME growth is through the use of websites for digital promotion and marketing. This article describes the website design process for the MSME